I Have Many Skills: Becoming the Xena of Teaching Modalities - Vaughan, Mariya; Coleman, Tara (My University, 2021)
While COVID-19 cases rose throughout the spring and summer months, faculty were expected to create flexible and engaging online learning environments, as many understood that courses would not represent the common classroom experience that students hope for as they begin college. Much like the titular warrior princess Xena, who faced overwhelming challenges and honed her impressive multitude of skills, faculty quickly learned and integrated new online teaching strategies and created varying new course modalities. Together we’ll explore the skills we’ve built and challenges we’ve faced that can be integrated into first-year courses moving forward through pandemic teaching and beyond.
Keywords: COVID 19; Online learning; Teaching modalities; Xena, warrior princess; Teaching strategies; First-year experience